Darwin’s Deadly Legacy? Why Evolution Matters for Management Studies - Yang, Chulguen; Colarelli, Stephen M.; Holston, Kayong (Research Yearbook, 2010)
Keywords: dept.mgt; peer-reviewed

Using Action Research to Build a Learning Organization in a New School of Pharmacy. - Hopkins, Pamela (2010)
Keywords: dept.mgt; faculty_collection; sabbatical_report

The Role of Chance in CEO Selection. - Stepanovich, Paul (2010)
Keywords: dept.mgt; faculty_collection; sabbatical_report

The green MBA: a competing values matrix - Page, Robert A; Collins, Kirsten A (Competitiveness Review: An International Business Journal Incorporating Journal of Global Competitiveness, 2010)
Purpose – The purpose of this paper is to review and categorize the different strategies Master of Business Administration (MBA) programs have adopted towards incorporating environmental sustainability into business administration. Design/methodology/approach – Through extensive internet research looking at colleges and universities, data are collected from primary source web sites and administrative school contacts. There are 35 institutions whose MBA programs address sustainability in some way. Each of these institutions is then organized by location, tuition cost, enrollment, year founded, accreditation, and curriculum. Findings – Green educational strategies differentiate themselves by the size and maturity of the program. Larger, established institutions typically opt for the green major, or a dual degree, and tend to leave systematic integration of sustainability to the individual student. Newer and smaller entrants tend to either dabble in green with a few sustainability courses, or completely embrace and systemically integrate sustainability throughout the program. Research limitations/implications – The sample focuses on US institutions and treats sustainability as an externally validated curricular choice when it may merely be an educational fad. The sample excludes potential green MBA programs that lack a strong internet presence. Practical implications – Four archetypes are identified: dual degree, all-green, green major, and green coursework. Institutions can analyze their performances and see where they fall on the two major continua – integration and maturity/size. Originality/value – Green MBA programs are relatively new on the academic landscape, and this research paper is one of the first to systematically analyze and categorize them. © Emerald Group Publishing Limited.
Keywords: Curricula; Economic sustainability; Education; Environmental studies; Master of business administration; dept.mgt

Biased against whom? The problems of “Group” definition and membership in test bias analyses - Colarelli, Stephen M; Han, Kyunghee; Yang, Chulguen (Industrial and Organizational Psychology, 2010)
Keywords: dept.mgt